1997
DOI: 10.1177/08959374970110010501
|View full text |Cite
|
Sign up to set email alerts
|

Growth Dynamics in a Natural Biofilm and Its Impact on Oral Disease Management

Abstract: Measurements of the microbial growth dynamics in natural biofilm communities are almost non-existent. In a recent study, the biofilm formation on teeth was examined. A previously unknown active period of bacterial division occurred at a certain density of plaque bacteria on tooth enamel. The density-dependent cell-division phase of plaque formation contributed 90% of the biomass in the first 24 hrs of plaque formation. This suggested that growth was induced by the bacteria. In vitro assays were developed for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…During this active accumulation phase, the number of biofilm cells increased exponentially, which accounted for most of the biomass in the first 20 h of cell accumulation. A similar active accumulation phase of S. gordonii in an in vivo model was also noted by Bloomquist et al (2) and Liljemark et al (31), who found that density-dependent cell multiplication contributes to 90% of the biomass in the first 24 h of dental plaque formation. These authors also showed that a cell-free supernatant taken from growing S. gordonii cultures could induce an exponential increase in the incorporation of [ 3 H]methyl-thymidine into biofilm cells, suggesting that a cell-cell signaling mechanism was activated.…”
Section: Discussionsupporting
confidence: 52%
“…During this active accumulation phase, the number of biofilm cells increased exponentially, which accounted for most of the biomass in the first 20 h of cell accumulation. A similar active accumulation phase of S. gordonii in an in vivo model was also noted by Bloomquist et al (2) and Liljemark et al (31), who found that density-dependent cell multiplication contributes to 90% of the biomass in the first 24 h of dental plaque formation. These authors also showed that a cell-free supernatant taken from growing S. gordonii cultures could induce an exponential increase in the incorporation of [ 3 H]methyl-thymidine into biofilm cells, suggesting that a cell-cell signaling mechanism was activated.…”
Section: Discussionsupporting
confidence: 52%
“…The logarithmic increase in cell numbers on the surfaces during this phase could be attributed to the growth of biofilm cells, since adherence alone did not result in a logarithmic increase in cell numbers on surfaces (27). A similar cell density-dependent multiplication during biofilm formation in S. gordonii was previously demonstrated by Liljemark et al (28), who observed DNA synthesis using a [methyl-…”
Section: Discussionmentioning
confidence: 49%
“…Initial colonization of enamel surfaces by bacteria occurs in 3 stages: saturation of pellicular binding sites, accumulation of organisms via a variety of mechanisms until a critical density is reached, and density-dependent growth. 27 Several studies 1,25,26 have suggested that oropharyngeal colonization plays an important role as a reservoir of nosocomial colonization and support the hypothesis that antiseptic decontamination of dental plaque might decrease the rate of acquired nosocomial infection in ICU adult patients. However, few data support this hypothesis for infants and children, and we found that in children in a PICU, the effects of oral care consisting of mechanical intervention plus chlorhexidine did not differ from the effects of oral care consisting of mechanical intervention alone.…”
Section: Oropharyngeal Colonizationmentioning
confidence: 90%